THE EFFECT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) ON THE INCREASING SPIRIT OF PARAMEDIC WORK OF COMMUNITY HEALTH CENTER IN EAST OKU DISTRICT - Helisia Margahana; Wahid Eka Saputra; Demsi Harlofida; Yansahrita . (UNIVERSITAS PAKUAN, 2020)
Morale of a person will be influenced by the level of job satisfaction they have. When an employee feels satisfied with the work being done, the employee will work optimally in completing his job, even doing some things that may be outside his job. The problem faced by community health center paramedics in East OKU district is how the Organization Citizenship Behavior plays an important role in the morale of public health center paramedics in East OKU district, while this research is to determine the important role of Organization Citizenship Behavior on the performance of Paramedics. Community health center in East OKU Regency. The hypothesis proposed is that there is a strong influence between Organization Citizenship Behavior on the performance of public health center paramedics in East OKU Regency.From the calculation results obtained r = 0.689. After being consulted with conservative standards to determine whether the relationship is close or not, it turns out that it lies in the distance between 0.600 - 0.799. It can be concluded that the influence of Organization Citizenship Behavior on improving the performance of community health center paramedics in East OKU Regency is having a strong influence. Then to answer the hypothesis test that was previously proposed to have a relationship or not, then tested with the hypothesis test and obtained t count = 2.69. While the value of t table at the 95% confidence level for (n - 2) = 1,860. Then it can be seen that the value of t count 2.74 is greater than the value of t table, namely = 1.860, thus means (Ha) can be accepted and (Ho) is rejected. This means that the hypothesis proposed is acceptable, namely the influence of the Organization Citizenship Behavior on increasing the morale of Puskesmas Paramedics in East OKU Regency is very strong